Isotopic Composition Reveals the Impact of Oyster Aquaculture on Pelagic Nitrogen Cycling in a Subtropical Estuary. (15th December 2020) - Jiang, Hao; Lan, Wenlu; Li, Tianshen; Xu, Zhifang; Liu, Wenjing; Pan, Ke
Highlights: An isotope approach was used to evaluate the impact of oyster aquaculture on pelagic N cycling. Intensive oyster aquaculture greatly increased pelagic nitrification in the bay. Oyster biodeposits comprised a major portion of the suspended particulate organic matter. Oysters significantly contribute to the pelagic N pools and transformations in the estuary. Abstract: To offset estuarine eutrophication, interest is increasing in restoring oyster reefs and expanding oyster aquaculture. However, ecosystem-scale evidence is lacking on oyster assemblages' impacts on estuarine pelagic nitrogen (N) cycling. Using a multiple-isotope approach and isotope-mixing model, we examined the sources, transformations, and influence of intensive oyster aquaculture on N pollution in a subtropical estuary. The salinity-dependent NO3 – and NH4 + concentrations and their correlations with isotopic signals (δ 15 N-NO3 –, δ 18 O-NO3 –, δ 15 N-NH4 + ) indicated the nutrient spatial distribution in low-salinity areas was largely regulated by mixing between freshwater and seawater. However, the intensive oyster aquaculture greatly increased nitrification in the estuary. In high-salinity areas where oyster assemblages were absent, the assimilation of NO3 – by phytoplankton became dominant and sharply increased the δ 15 N-NO3 – and δ 18 O-NO3 – . Soil organic nitrogen and fertilizer, domestic sewage, and wastewater treatment plants were the major NO3 – sources in the estuary, while internal nitrification contributed 20.6% to the NO3 – pool. Oyster biodeposits comprised up to one-third of the particulate organic matter in the water column, and as much as 47.3% of the NH4 + pool could be from the oysters. Our study shows that oysters significantly contribute to the pelagic nutrient pools and N transformations, adding an important dimension to our understanding of oyster assemblages' impacts on estuarine N cycling. Graphical abstract: Image, graphical abstract